Coronavirus and the puerperium: a case report - Lucas R. Mostardeiro; Luiza G. Schmitt; Jady W. Xavier (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT COVID-19 started in China on December 31, 2019 and has since been the subject of several studies in medical field. There is not much evidence about the pregnancy and puerperium with the susceptibility of coronavirus infection (COVID-19). The present work reports the laboratory and radiological aspects of a puerperium patient. A positive test for severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) generally confirms the diagnosis of COVID-19, although false-positive and false-negative tests are possible. The test considered the gold standard for the diagnosis of coronavirus infection (COVID-19) is from in vivo or post-mortem polymerase chain reaction (PCR) sample. The purpose of the present case report is to demonstrate the case of a puerperium patient with an unfavorable clinical evolution, giving special attention to laboratory tests that were practically unchanged.